HIERARKI DAN INFORMALITAS SOSIAL PADA PRODUKSI RUANG DI NAGARI PARIANGAN, SUMATERA BARAT - Juli Yanda Putra; Agus S. Ekomadyo (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2022)
Abstract: Nagari Pariangan is an old village in Minangkabau, West Sumatra. Nagari is a customary law community unit consisting of a collection of several tribes and has its own territorial boundaries. The phenomenon of the nagari shows the production of social space based on Minangkabau villages culture. The purpose of this paper is to determine the relationship between the architectural elements of Nagari Pariangan and their relationship with their environment associated with the spatial production, uses Spatializing Culture approach (Low, 2017). Research is conducted by ethnographic approach data is collected by observation and in-depth interview. It is resulted, that the spaces of Nagari are formed mostly based on the social hierarchy of community, but also provided spaces for informal relationship. Political culture of the Nagari is important factor in governing spatial production by the traditonal community, but the other side, the community also produces their own communal spaces.Abstrak: Nagari Pariangan adalah nagari tuo yang ada di Minangkabau, Sumatra Barat. Nagari merupakan satu kesatuan masyarakat hukum adat yang terdiri dari kumpulan beberapa suku dan mempunyai batas wilayahnya sendiri. Fenomena Nagari menunjukkan adanya produksi ruang sosial berdasarkan budaya pada Nagari di Minangkabau. Tujuan dari penulisan ini adalah untuk mengetahui hubungan antara elemen arsitektur pembentuk Nagari Pariangan dan relasi sosial yang memproduksi ruang yang ditelaah melalui pendekatan Spatializing Culture (Low, 2017). Penelitian ini dilakukan dengan pendekatan etnografi, data dikumpulkan lewat observasi dan wawancara mendalam. Ditemukan, ruang-ruang Nagari terbentuk berdasarkan hierarki sosial, namun tetap tersedia ruang-ruang informal. Budaya politik dari Nagari menjadi faktor terpenting dalam tata kelola produksi ruang oleh komunitas adat, namun di sisi lain, komunitas Adat juga memproduksi ruang-ruang komunalnya sendiri.